Przemiany władzy lokalnej: [Transformations of local power] (Studia Prawnicze / The Legal Studies, 1981)
Local power, understood as representation of the population and local govern- ment, constitutes the subject matter of this article. Necessity of taking notice of the relation between democracy and organization of both central and local power, was pointed out already in inter-war period, unfortunately more in theory than in practice. As an example, Polish constitutional solutions are cited: those of 1921 and 1935, and the practice of functioning of local government. Limitation of competences of local power was a tendency observed in many countries, and the renaissance of self-governing concepts was linked with the fall of totalitarian systems. In many european countries, both socialist and bourgeois, problems concerning local power are considered main political and structural problems and the search for the best solution to shape the relations between central and local powers is still going on. Solutions of a bourgeois state bring new experience as far as competences of local power are concerned, among others, those of regionalization. In a socialist state local government and wide competences of local powers constitute one of the fundamental principles on which socialist model of representation is based.Concepts concerning the position of 'local power in relation to central one have undergone evolution; as far as People’s Poland is concerned this process begun during the period of National Country Council and is continued until today. Notwithstanding all structural differences, the practice of everyday political life proves that local government is irreplaceable if we want to realize a de- mocratic system. In a socialist state, wide concepts of local power lie at the basis of theoretical concepts concerning exercise of power - thus the tendency to increase participation of the citizens in governing and to create such relations between central and local powers which would promote the realization of socialist democracy.